Utilization of Drepansotachyum falcatum (Nees) Keng F. (Hill Bamboo) for Generating Economy by Some Scheduled Caste Families in Homesteads of Pithoragarh District, Uttarakhand - Arya, Vijay; Kumar, Balwant; Gosain, Bharat Giri (Indian Forester, 2015)
Drepanostachyum falcatum (Arundinaria falcata Nees) is a common species of hill bamboo locally called Ringal is abundantly found in the homesteads. Four representative villages i.e., Kothera, Balakuncha, Guptari and Bhainskot of Pithoragarh district were selected for the study. The dwellers of the area are acquainted with the utilization of this important species of hill bamboo for generating income. Some scheduled caste families of the area have taken big efforts using D. falcatum for the sustenance of their livelihood. They have a potential to play a big role in handicraft sector and thereby contributing in the economy of the region as well as of the state. The present study was carried out to assess the indigenous knowledge on the usage of D. falcatum for generating economy by some scheduled caste families of rural communities in Pithoragarh district, Kumaun Himalaya. Paper emphasizes the source and quantity of raw material,total number of articles preparedby the artisans and income generated using this bamboo.